The Role of Corticosteroids in Treating Acute Ocular Toxoplasmosis in an Immunocompetent Patient: A Case Report - Lin, Hung-Yi; Lee, Wan-Ju Annabelle (Frontiers in Medicine, 2022)
Background: This study aimed to report a case who was treated with corticosteroid and anti- parasitic agents for the ocular toxoplasmosis, but progressed to acute retinal necrosis, and finally retinal detachment. Case Presentation: A 42-year-old man presented to the ophthalmology clinic with a 1-month history of progressive blurred vision and floaters in his right eye. His best visual acuity (VA) was 20/20 in both eyes. The anterior segment was unremarkable. Fundoscopic examination of the right eye revealed active lesions of whitish foci of chorioretinitis with surrounding edema along the superonasal vessels, and retinal vasculitis with perivascular sheathing. Serologic testing was positive for Toxoplasma gondii IgM and IgG, but negative for other virus and syphilis infections. Ocular toxoplasmosis was diagnosed. Corticosteroid and anti-parasitic agents were given simultaneously, but his right eye VA became 20/100. Fundoscopic examination revealed retinal necrosis with localized retinal breaks. We performed focal photocoagulation immediately, however, his right eye progressed to retinal detachment and required vitrectomy. Conclusion: Early administration of systemic corticosteroid in patients with acquired acute ocular toxoplasmosis may lead to potential complications that impaired vision. Intensive observation should be arranged after corticosteroid use.